2005
DOI: 10.1097/01.aog.0000163253.27610.b9
|View full text |Cite|
|
Sign up to set email alerts
|

Endometrial Effects of Bazedoxifene Acetate, a Novel Selective Estrogen Receptor Modulator, in Postmenopausal Women

Abstract: Bazedoxifene at dosages up to 40 mg/d was well tolerated and did not stimulate the endometrium. The significant decreases in endometrial thickness and decreased uterine bleeding observed with doses of 30 and 40 mg/d as compared with placebo suggest endometrial antagonism, representing a novel characteristic not previously associated with any selective estrogen receptor modulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 20 publications
2
61
0
1
Order By: Relevance
“…Based on endometrial protective properties of BZA observed in preclinical and clinical evaluations (11)(12)(13), it was hypothesized that a TSEC composed of BZA/CE would provide effective relief of menopausal symptoms with a high level of endometrial safety and a favorable tolerability profile. Findings from this phase III trial indicate that TSECs composed of BZA/CE at dose combinations of BZA 20 and 40 mg with CE 0.45 and 0.625 mg are associated with an amenorrhea profile similar to that observed with placebo, suggesting that BZA/CE may offer a favorable tolerability profile.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Based on endometrial protective properties of BZA observed in preclinical and clinical evaluations (11)(12)(13), it was hypothesized that a TSEC composed of BZA/CE would provide effective relief of menopausal symptoms with a high level of endometrial safety and a favorable tolerability profile. Findings from this phase III trial indicate that TSECs composed of BZA/CE at dose combinations of BZA 20 and 40 mg with CE 0.45 and 0.625 mg are associated with an amenorrhea profile similar to that observed with placebo, suggesting that BZA/CE may offer a favorable tolerability profile.…”
Section: Figurementioning
confidence: 99%
“…Preclinical studies (11,12) also showed that BZA inhibits 17b-E 2 -induced proliferation of MCF-7 human breast cancer cells in a dose-dependent manner. Daily doses of 2.5, 5.0, 10, 20, 30, and 40 mg BZA in a phase II study (13) were generally well tolerated and were not associated with endometrial stimulation compared with placebo. Further, BZA 30 and 40 mg were associated with significantly smaller mean increases in endometrial thickness and significant decreases in uterine bleeding compared with placebo (P<.05) (13), suggesting estrogen antagonist activity in the endometrium.…”
mentioning
confidence: 98%
“…A recent report of a 2 year study revealed that BMD of the lumbar spine and hip were significantly greater with bazodoxifene than with placebo for all the various doses. There was reduced bone turnover and prevention of bone loss similar to raloxifene [51]. The significant differences were apparent at 6 months with bazodoxifene versus placebo and were maintained up to the 24th month.…”
Section: Serms Under Developmentmentioning
confidence: 84%
“…No difference in endometrial thickness was found in a randomized clinical trial of approximately 500 women with an intact uterus [6]. No difference in endometrial thickness was found between bazedoxifene and placebo.…”
Section: Phase 2 Studiesmentioning
confidence: 88%